Syntheses of higher education research : what we know - Tight, Malcolm (London, England : Zed Books, 2020)
"Bringing together over 96 systematic reviews and 62 meta-analyses focusing on particular topics in higher education research, Tight explores key topics: teaching and learning, course design, the student experience, quality, system policy, institutional management, academic work, and knowledge and research. These systematic reviews and meta-analyses give an account of where we are now in higher education research and Tight draws their findings together to provide an accessible and practical overview of the field"--
Introduction -- Research syntheses -- Research syntheses in higher education research -- Teaching and learning -- Course design : types of instruction -- Course design : types of learning -- Course design : distance, online and e-learning -- Course design : curriculum -- Course design : assessment -- Course design : outcomes -- The student experience -- Quality -- System policy -- Institutional management -- Academic work -- Knowledge and research -- Conclusion.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Education, Higher -- Research; Education, Higher -- Evaluation; Colleges of higher education; Electronic books